Effectiveness of behavioral interventions and behavior change techniques for reducing soft drink intake in disadvantaged adolescents: A systematic review and meta‐analysis - S. S. Shagiwal; E. Groenestein; A. Schop‐Etman; J. Jongerling; J. van derWaal; G. Noordzij; S. Denktas (Wiley, 2020)
Summary Reducing sugar‐sweetened beverage (SSB) intake is an important dietary target, especially among socioeconomically disadvantaged ethnic minority adolescents. This review and meta‐analysis evaluated the effectiveness of behavioural interventions aiming to reduce SSB intake in socioeconomically disadvantaged ethnic minority adolescents and examined which behaviour change techniques (BCTs) were most effective. A systematic search was conducted using the PRISMA criteria. Quality assessments were done using the Cochrane criteria. In a narrative synthesis, studies were divided into effective and non‐effective, and relative effectiveness ratios of individual BCTs were calculated. Pooled standardized mean differences (SMDs) and their 95% confidence intervals were estimated with random‐effects models using cluster robust methods. Twenty‐two studies were included in the qualitative synthesis. A meta‐analysis (n = 19) revealed no significant between‐group differences in reduction of SSB intake. Five self‐regulatory BCTs had an effectiveness ratio >50%: feedback, goal‐setting, action planning, self‐monitoring and problem‐solving/barrier identification. The risk of bias assessments were judged to be moderate to high risk for randomized controlled trials (RCTs) studies and low to moderate for pre-post studies. There was no indication of publication bias. In conclusion, self‐regulatory BCTs may be effective components to change SSB behaviour. However, high‐quality research is needed to evaluate the effectiveness of behavioural interventions and identify BCTs effective for reducing SSB intake among disadvantaged adolescents with ethnic minority backgrounds.